Anti-CD74 IGA antibodies, genetic polymorphisms and inflammatory activity in ankylosing spondylitis - V. I. Mazurov; I. Z. Gaydukova; E. A. Vasilenko; E. A. Vasilenko; S. V. Lapin; S. V. Lapin; I. V. Kholopova; M. A. Korolev (Научно-практическая ревматология)
IgA anti-CD74 can be a promising marker for diagnosis, assessment of activity and prognosis for ankylosing spondylitis.The aim of the study was to determine the level of IgA anti-CD74 in patients with ankylosing spondylitis and to evaluate its relationships with ankylosing spondylitis activity and carriership of genetic alleles.Materials and methods. In 48 patients with a reliable diagnosis of ankylosing spondylitis, aged 18 to 69 years were measured the ASDAScrp, BASDAI, level of highly sensitive С-reactive protein, concentration of IgA anti-CD74. The polymorphisms of the genes interleukin (IL)-17A197 a/g, IL-17F7 histidine (His) / arginine (Arg), IL-17F11139 c/g, TNF-a-863, TNFα-308, TNFα-238, IL-1B-31, IL- 4-590, IL-6-174, IL-10-1082, IL-10-592, vascular endothelial growth factor (VEGF)-2578, VEGF-936, matrix metalloproteinase (MMP)2-1306, MMP3-5A6A, MMP9-1562, HLA-B27 were evaluated in their relationships with AS activity and IgA anti-CD74 levels.Results. The mean age of patients was 45.1±14.2 years, male - 72.9%, psoriasis - 10.4%, IBD - 2.1%, BASDAI -2.99±0.28, ASDAS - 2.29±0.16, CRP - 6.5±1.65 mg/L, IgA эпй-СВ74 - 18.6±1.73 U/mL (72.9% of the patients with >12 U/mL). The relationship between an increase in concentration of IgA anti-CD74 and ASDAScrp, BASDAI activity indices, between an increase in the level of CRP and the presence of the IL-17A genotype heterozygous for the AA allele (r=0.965) was determined. CRP did not demonstrate the relationship with the BASDAI.An association of IL-17F-11139 СС and the presence of psoriasis (r=0.870) was established. 93.8% of patients with ankylosing spondylitis were carriers of the homozygous histidine allele IL-17F7 (his/his) and the TNF238 allele (GG).Conclusions. The increase in anti-CD74 IgA level was found in 72.9% of patients with ankylosing spondylitis receiving inhibitors of TNF-a and NSAIDs and associated with clinical and laboratory indicators of ankylosing spondylitis activity and with carriage of the homozygous histidine allele IL-17F7 (his/his) detected in 93.8% of patients. Carriage of TNF-238 GG; TNF-863 CC; HLA-B27; TNF-308 GG; IL-4-590 CC; IL-6-174 CG;MMP9-1562 CC; MMP9-1562 CC; VEGF- 936 CC alleles was not associated with an increase in concentration of IgA anti-CD74. CRP demonstrated an association with IL-17A-197 AA (r=0.965) detected in 29.2% of patients with no correlation with the clinical ankylosing spondylitis activity in patients receiving treatment with iTNF-α and NSAIDs.